De ziel van mijn schoon Kempenland - Wellens, Charles (Hasselt : De Limburgse Drukkerijen, 1951)
Bibliotheek Camille Huysmans
Nederlands
Frans
Brochure
Keywords: landbouwers; schilderkunst; Kempen; Limburg